Retroperitoneal Hemorrhage After Sacral Neurostimulator Placement for Urgency Urinary Incontinence. Issue 4 (July 2017) - Kinman, Casey L.; Hobson, Deslyn T.G.; Agrawal, Anubhav; Vyleta, Martin S.; Francis, Sean L.
Abstract : Abstract: Sacral neuromodulation (SNM) is an effective therapy for patients who experience urinary incontinence, idiopathic urinary retention, and fecal incontinence. Although typically a low-risk procedure, rarely, it can be associated with significant hemorrhage. A 61-year-old woman on chronic anticoagulation underwent uncomplicated implantation of SNM for refractory urgency urinary incontinence. Anticoagulation was held on the day of surgery and resumed on postoperative day 1. On postoperative day 2, the patient developed an extensive retroperitoneal hemorrhage. This was successfully treated by angioembolization of the left lateral sacral artery with the InterStim device left in situ. At 6-month follow-up, the device was functioning properly, and the patient's urinary symptoms were well controlled. Retroperitoneal hemorrhage is a rare complication after SNM placement. Conservative management with angioembolization should be considered as a first-line approach. Abstract : Extensive retroperitoneal hemorrhage following sacral nerve stimulator placement can be treated successfully with angioembolization.